Instytucjonalizacja strategicznego controllingu jako system zarządzania w przedsiębiorstwie - Pogodina, Wiera W.; Owczinnikowa, S. G. (Institutionalisation of Strategic Controlling as a Management System in an Enterprise, 2008)
The paper describes controlling as a management system. The emphasis is put on the strategic significance of controlling and the necessity to its institutionalisation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 296-302